2019
DOI: 10.7717/peerj.6947
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the National Early Warning Score (NEWS) and the Modified Early Warning Score (MEWS) for predicting admission and in-hospital mortality in elderly patients in the pre-hospital setting and in the emergency department

Abstract: The aim of this study is to evaluate the usefulness of the pre-hospital National Early Warning Score (pNEWS) and the pre-hospital Modified Early Warning Score (pMEWS) for predicting admission and in-hospital mortality in elderly patients presenting to the emergency department (ED). We also compare the value of the pNEWS with that of the ED NEWS (eNEWS) and ED MEWS (eMEWS) for predicting admission and in-hospital mortality. This retrospective, single-centre observational study was carried out in the ED of Jikei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 17 publications
3
60
1
5
Order By: Relevance
“…26 EWSs, which are generally used in the patients with sepsis, trauma, and other critical ills, are such scoring systems and are widely used in hospitals to identify patients who are clinically deteriorating. 17,20,27,28 On the whole, the performance of each EWS was acceptable for screening the COVID-19 patients. However, there are differences in the performance among 5 EWSs.…”
Section: Figurementioning
confidence: 95%
“…26 EWSs, which are generally used in the patients with sepsis, trauma, and other critical ills, are such scoring systems and are widely used in hospitals to identify patients who are clinically deteriorating. 17,20,27,28 On the whole, the performance of each EWS was acceptable for screening the COVID-19 patients. However, there are differences in the performance among 5 EWSs.…”
Section: Figurementioning
confidence: 95%
“…Hospital administrators can implement the SIPI measure to identify those patients, units or departments that require a major amount of nursing care, particularly when recommended staffing levels cannot be assured due to lack of resources. Future studies should: assess the association between complexity of nursing care and in-hospital mortality in surgical settings; assess the association between the complexity of nursing care measured by the SIPI score and in-hospital mortality, adjusting for nursing-related variables as staffing, skill mix and education; assess the relationship between complexity of nursing care and widely used early warning scores such as the National Early Warning Score [5]; identify the different levels of nurse staffing according to the complexity of nursing care as measured by the SIPI; assess the association between Diagnosis Related Groups (DRGs) and complexity of nursing care, in order to investigate if the current approach in allocating resources takes into account the demand of nursing care.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies explored those predictors focusing on patients' clinical characteristics. Comorbidity [4], clinical instability [5] and baseline functional status [6] were found to be strong predictors of inhospital mortality. Other studies focused on the severity of a specific admission disease or condition.…”
Section: Introductionmentioning
confidence: 93%
“…( 7 ) Recent studies have shown high variability in the accuracy of this score, which has led to uncertainty regarding its use. ( 2 , 4 , 9 , 10 ) Its role in the inter- or intrahospital transfer of patients is even more undefined. Although it has been applied in interhospital pretransfer, ( 11 - 13 ) its use at the time of transfer between sectors of the same hospital has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%